Pengaruh Efikasi Diri Dan Motivasi Berprestasi Terhadap Kesiapan Belajar Mandiri Mahasiswa - Mufidah, Elia Firda; Wahyuni, Fitri; Pravesti, Cindy Asli; Setyaputri, Nora Yuniar; Ariyanto, Restu Dwi; Dwiyana, Artiyan (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
Changes in learning patterns put demands on students with a state of believing in their own abilities, believing in their ability to grow, encouraging curiosity, encouragement to want to succeed, encouragement to cooperate, initiative, perseverance, and independence. For this reason, the purpose of this study is to determine the effect of self-efficacy and achievement motivation on self-directed learning readiness. The research design used is quantitative with a correlational design. The number of samples in this study were 488 students. The instruments used are self-efficacy scale, achievement motivation scale, and self-directed learning readiness. The data analysis in this study is multiple regression analysis by going through the assumption test as a prerequisite. The results of the assumption test which include normality and heteroscedasticity have been declared eligible. Then, on the results of multiple regression analysis with the value of t count > t table, the self-efficacy value of 12,060 > 2,248 means that H1 is accepted. Furthermore, the value of achievement motivation is 5.992 > 2.248, which means that H2 is accepted. In the simultaneous F test with a calculated F value of 90.524 > F table of 1.195, which means that H3 is accepted, this means that simultaneously self-efficacy and achievement motivation affect the self-directed learning readiness. It can be concluded that self-directed learning readiness students’ increases due to their self-efficacy and encouragement to achieve goals or achievement motivation. Thus, based on the purpose of this research, it is possible to contribute in the form of self-directed learning readiness students to facilitate the educational process in any situation.